2006
DOI: 10.1266/ggs.81.155
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to maintain the stability of the ribosomal RNA gene repeats -Collaboration of recombination, cohesion, and condensation-

Abstract: Ribosomal RNA gene repeats (rDNA) are one of the most characteristic regions in eukaryotic chromosomes. The repeats consist of more than 100 tandem units occupying large part of the chromosome in most of organisms. Cells are known to deal with this "unusual domain" in a unique manner. In this review, I will summarize work on rDNA repeat maintenance, focusing mainly on work done by our group, and show that the maintenance mechanism operates by a collaboration of recombination, sister-chromatid cohesion, and chr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
82
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(86 citation statements)
references
References 43 publications
4
82
0
Order By: Relevance
“…FAS/FAS, wild type; fas/ fas, mutant. Kobayashi, 2006;Labib and Hodgson, 2007;Tsang and Carr, 2008). Although the mechanism of rDNA copy number maintenance in plants has not been described so far, the replication fork barriers have been documented in plants (Hernandez et al, 1993;Lopez-Estrano et al, 1999), and the intergenic spacer of the 45S rDNA has been identified as a recombination hot spot (Urawa et al, 2001).…”
Section: Telomere Shortening and Chromosome-end Deprotectionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAS/FAS, wild type; fas/ fas, mutant. Kobayashi, 2006;Labib and Hodgson, 2007;Tsang and Carr, 2008). Although the mechanism of rDNA copy number maintenance in plants has not been described so far, the replication fork barriers have been documented in plants (Hernandez et al, 1993;Lopez-Estrano et al, 1999), and the intergenic spacer of the 45S rDNA has been identified as a recombination hot spot (Urawa et al, 2001).…”
Section: Telomere Shortening and Chromosome-end Deprotectionmentioning
confidence: 99%
“…Although the mechanism of rDNA copy number maintenance in plants has not been described so far, the replication fork barriers have been documented in plants (Hernandez et al, 1993;Lopez-Estrano et al, 1999), and the intergenic spacer of the 45S rDNA has been identified as a recombination hot spot (Urawa et al, 2001). Whereas the yeast 5S rDNA is subjected to joint copy number regulation as a part of the 35S rDNA locus (Kobayashi, 2006), the separate localization and possibly different regulation of the 45S and the 5S rDNA loci in Arabidopsis may explain the selective loss of the 45S and not the 5S rDNA in the fas mutants (Figure 3; see Supplemental Figure 7 online). Since dysfunction of CAF1 in plants has been connected to increased numbers of DNA DSBs, increased level of HR, and upregulation of genes involved in HR (Endo et al, 2006;Kirik et al, 2006;Schonrock et al, 2006;Ramirez-Parra and Gutierrez, 2007), it is possible that disruption of a recombination-based maintenance equilibrium may lead to the 45S rDNA loss.…”
Section: Telomere Shortening and Chromosome-end Deprotectionmentioning
confidence: 99%
“…SSA is thought to be the predominant form of DSB repair within highly repetitive regions of the genome, such as the ribosomal DNA (Kobayashi 2006;Li et al 2008;George and Alani 2012), and limits unavoidable loss of genetic information to local deletions rather than large-scale rearrangements. It could also offset repeat expansions in these regions.…”
mentioning
confidence: 99%
“…However, the DNA sequence and structure itself also determines the fidelity of genome propagation, with each class of repeat DNA (i.e., ribosomal DNA, telomeres, trinucleotide repeats, and transposons) presenting unique challenges to the genome. There are pathways that predominate to ensure control of each repeat type [e.g., chromatin cohesion and transcriptional silencing are needed to stabilize ribosomal DNA repeat copy number whereas trinucleotide repeat array integrity depends on accurate DNA replication and mismatch repair (4,5)], but the precise interactions of repetitive DNA with the various DNA repair pathways remain unidentified.…”
mentioning
confidence: 99%